In Vivo Optical Properties of Melanocytic Skin Lesions: Common Nevi, Dysplastic Nevi and Malignant Melanoma - Zonios, George; Dimou, Aikaterini; Carrara, Mauro; Marchesini, Renato (Photochemistry and photobiology, 2010)
We present an in vivo study of the optical properties of common nevi, dysplastic nevi and malignant melanoma skin lesions in human subjects. Reflectance spectra were measured on 1379 skin lesions, in the visible and near‐infrared spectral regions, using a spectral imaging system, in a clinical setting. Analysis of the data using a reflectance model revealed differences between the optical properties of melanin present in nevi and melanoma lesions. These differences, which are in agreement with our previous observations on average reflectance spectra, may be potentially useful for the noninvasive characterization of pigmented skin lesions and the early diagnosis of melanoma.